Use of the electrocoagulation with pomegranate peels and zizith’s leaves adsorption coupling technique for removal of methylene blue in a batch system - Alnawab, Raghda M.; Ridha, Ali Mousa (International Journal of Engineering and Technology, 2018)
The present work is concerned with the remediation MB of aqueous solution by exploring the batch electrocoagulation process EC, and coupling the EC with biosorption on to pomegranate EC/PP and ziziphus EC/ZL. Batch experiments were conducted to investigate the EC, EC/PP, and EC/ZL processing at different parameters, such as, current density, pH, contact time and initial dye concentrations, NaCl concentration, distance between electrodes and biosorbents dosages for PP and ZL. The highest removal efficiency of EC (93.47%) was obtained at a current density of 21.440 A/m2, initial dye concentration of 100 mg/l, pH of 7, the NaCl concentration of 1.5 g/l, time of 60 minutes, and inter electrode distance of 1 cm. The energy consumption of electrodes was evaluated at these operating conditions to be 1.9 KW.h/m3. The maximum removal efficiency of the coupling treatment process EC/PP of 96% under optimum operating conditions of EC was achieved at 1500 mg of pomegranate peels, 30 min treatment time, and 1.3 KW.h/m3 of energy consumption of electrodes. From the comparison between EC, EC/PP, and EC/ZL techniques, it can be seen that the coupling technique EC/PP is the best method for removal of MB dye than EC and EC/ZL. The Langmuir isotherm fits the experimental data better than Freundlich and Temkin adsorption isotherm for the EC process alone, EC/PP and EC/Zl processes.